(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
This study aims to awaken thinking and stir debate around the future vision of the accounting profession in Alegria in endeavor to affiliate to World Trade Organization (WTO). So the study tries to touch the potential effects and the potential repercussions that could leave to join the future of this organization and the reflections that may result from this affiliation on the future and the practice of the accounting profession in Algeria. The study also takes in to consideration the main principles that state Member adhere to when they gain Membership in this organization, with shedding light on the effect of each principles of the accounting profession and its practitioners in Algeria. Keywords – World Trade Organization, the General Agreement on Trade in Services, the accounting profession